(untitled) (Historia, 2021)
Scholars who work in the humanities, especially those among us who do not do much quantitative research can often be daunted by data analysis and creating complex computer-generated visualisations. Digital humanities is growing, but it can seem that those involved in the field are cordoned off from researchers who do more classical analysis. What I would like to do in this short article is to focus on one tool in particular that I have used. It is simple, user friendly, free, powerful and perfect for those wishing to conduct analysis, GIS mapping and data visualisations without the daunting task of learning more advanced tools. The programme I shall focus on is Microsoft Power BI Desktop. To begin, I will first give an overview of the aspect of my research that resulted in finding and learning how to use this tool. I shall then review how I have used Microsoft BI and lastly, I shall review the tool’s limitations.